1994
DOI: 10.1161/01.hyp.23.1_suppl.i235
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a metalloendopeptidase-24.15. Inhibitor on renal hemodynamics and function in rats.

Abstract: /v"-[l-(ft.S)-carboxyl-3-phenylpropyl]-Ala-Ala-Phep-aminobenzoate (cFP-AAF-pAB), an active-site-directed inhibitor of metalloendopeptidase-24.15, has been shown to lower blood pressure, increase cardiac output and renal blood flow, and potentiate the intravenous bradykinin-induced vasodepressor response. Because in vivo cFP-AAF-pAB can be converted to A41-(R,S)-carboxyl-3-phenylpropyl]-Ala-Ala (a compound with angiotensin converting enzyme inhibitory activity) by metalloendopeptidase-24.11, it is possible that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 5 publications
1
12
1
Order By: Relevance
“…However, these effects are entirely attributable to inhibition of ACE by the metabolite cFP-AA (Telford et al, 1995;Lew et al, 1996). Similar observations have been made in anaesthetized rats in which the phenylalanine substituted analogue cFP-AAF-pAB was used (Yang et al, 1994). We can, however, be confident that the dose of cFP-AAY-pAB administered was sufficient to inhibit EP 24.15, since its plasma levels were orders of magnitude above its K, for EP 24.15 (16 nM; Orlowski et al, 1988).…”
Section: Effects Of Inhibition Of Ep 2415supporting
confidence: 72%
See 4 more Smart Citations
“…However, these effects are entirely attributable to inhibition of ACE by the metabolite cFP-AA (Telford et al, 1995;Lew et al, 1996). Similar observations have been made in anaesthetized rats in which the phenylalanine substituted analogue cFP-AAF-pAB was used (Yang et al, 1994). We can, however, be confident that the dose of cFP-AAY-pAB administered was sufficient to inhibit EP 24.15, since its plasma levels were orders of magnitude above its K, for EP 24.15 (16 nM; Orlowski et al, 1988).…”
Section: Effects Of Inhibition Of Ep 2415supporting
confidence: 72%
“…We can, however, be confident that the dose of cFP-AAY-pAB administered was sufficient to inhibit EP 24.15, since its plasma levels were orders of magnitude above its K, for EP 24.15 (16 nM; Orlowski et al, 1988). In terms of effects on renal function, our observations contrast with those of Yang et al (1994), who found that in rats pretreated with only the ACE inhibitor enalaprilat, cFP-AAF-pAB increased glomerular filtration rate, urine volume, and the fractional excretion of Na'. There are a number of possible reasons for this discrepancy, including differences in experimental conditions between the two studies.…”
Section: Effects Of Inhibition Of Ep 2415contrasting
confidence: 51%
See 3 more Smart Citations